Enhanced third‐order nonlinear optical properties determined in thin films using the Z‐scan technique: bis(μ‐4, 4′‐oxydibenzoato)bis[(4′‐phenyl‐2, 2′:6′, 2′′‐terpyridine)cobalt(II)]. Issue 5 (25th April 2016) - Liu, Runqiang; Zhao, Ning; Liu, Ping; An, Caixia; Lian, Zhaoxun
Abstract : A binuclear terpyridine cobalt(II) complex exhibits a very strong third‐order nonlinear optical saturable absorption (SA) in a thin film with an absorptive coefficient β of −37.3 × 10 −7 m W −1 . Abstract : π‐Conjugated organic materials exhibit high and tunable nonlinear optical (NLO) properties, and fast response times. 4′‐Phenyl‐2, 2′:6′, 2′′‐terpyridine (PTP) is an important N‐heterocyclic ligand involving π‐conjugated systems, however, studies concerning the third‐order NLO properties of terpyridine transition metal complexes are limited. The title binuclear terpyridine Co II complex, bis(μ‐4, 4′‐oxydibenzoato)‐κ 3 O, O ′: O ′′;κ 3 O ′′: O, O ′‐bis[(4′‐phenyl‐2, 2′:6′, 2′′‐terpyridine‐κ 3 N, N ′, N ′′)cobalt(II)], [Co2 (C14 H8 O5 )2 (C21 H15 N3 )2 ], (1), has been synthesized under hydrothermal conditions. In the crystal structure, each Co II cation is surrounded by three N atoms of a PTP ligand and three O atoms, two from a bidentate and one from a symmetry‐related monodentate 4, 4′‐oxydibenzoate (ODA 2− ) ligand, completing a distorted octahedral coordination geometry. Neighbouring [Co(PTP)] 2+ units are bridged by ODA 2− ligands to form a ring‐like structure. The third‐order nonlinear optical (NLO) properties of (1) and PTP were determined in thin films using the Z‐scan technique. The title compound shows a strong third‐order NLO saturable absorption (SA), while PTP exhibits a third‐order NLO reverse saturable absorption (RSA). The absorptive coefficient β of (1) is −37.3 × 10 −7  m W −1, which is larger than that (8.96 × 10 −7  m W −1 ) of PTP. The third‐order NLO susceptibility χ (3) values are calculated as 6.01 × 10 −8  e.s.u. for (1) and 1.44 × 10 −8  e.s.u. for PTP.